Learning Models for Traumatic Brain Injury Mortality Prediction on Pediatric Electronic Health Records - Fonseca, João; Liu, Xiuyun; Oliveira, Hélder P.; Pereira, Tania (Frontiers in Neurology, 2022)
Background: Traumatic Brain Injury (TBI) is one of the leading causes of injury related mortality in the world, with severe cases reaching mortality rates of 30-40%. It is highly heterogeneous both in causes and consequences, complicating medical interpretation and prognosis. Gathering clinical, demographic and laboratory data to perform a prognosis requires time and skill in several clinical specialties. Machine learning (ML) methods can take advantage of the data and guide physicians towards a better prognosis and, consequently, better healthcare. The objective of this work was to develop and test a wide range of machine learning models and evaluate their capability of predicting mortality of TBI, at hospital discharge, while assessing the similarity between the predictive value of the data and clinical significance. Methods: The used dataset is the Hackathon Pediatric Traumatic Brain Injury (HPTBI) dataset, composed of electronic health records containing clinical annotations and demographic data of 300 patients. Four different classification models were tested, either with or without feature selection. For each combination of classification model and feature selection method, area under the receiver operator curve (ROC-AUC), balanced accuracy, precision and recall were calculated. Results: Methods based on decision trees perform better when using all features (Random Forest, AUC=0.86 and XGBoost, AUC=0.91) but other models require prior feature selection to obtain the best results (k-Nearest Neighbours, AUC=0.90 and Artificial Neural Networks, AUC=0.84). Additionally, Random Forest and XGBoost allow to assess the feature importance, which could give insights for future strategies on the clinical routine. Conclusion: Predictive capability depends greatly on the combination of model and feature selection methods used but, overall, ML models showed a very good performance in mortality prediction for TBI. The feature importance results indicate that predictive value is not directly related to clinical significance.